Dangerous metaphor: The fiction of the labor market ; unemployment, inflation, and the job structure - James K. Galbraith (Levy Economics Institute of Bard College, 1997)
The concept of a labor market, responding to familiar underpinnings of supply and demand, completely colors thought on the relationship between employment, wages, and inflation, according to James K. Galbraith. However, he asserts, wages are determined not by such market forces, but by what he calls the job structure - a complex set of status and pay relationships involving individual qualifications, job characteristics, and industry patterns. What is the meaning of the job structure for policy? Notions of natural rates of unemployment and inflationary barriers to full employment fade away. Supply-side measures can no longer been seen as adequate to deal with problems of unemployment and inequality. Questions of distribution of income and adjustment of the wage structure are returned to the political context. The active pursuit of full employment is returned to the list of respectable, and essential, policy goals.
Keywords: 330